The development of temporal Cognition in children: (A developmental study) - Al-Hamdani, Hussein Abdullah Taher; Mansour, Huda Kamel (Al-Adab Journal, 2021)
This study aims at the measurement of the development of chronological cognition Children aged 7 to 11 years old. In Nasiriyah, the center of Dhi Qar governorate, for the year (2019-2020). The sample of the study included (150) children, by (75) male and (75) female. The researcher approved the test (DeNigris, 2017) and the theory model (McCormack, 2015) to measure temporal cognition in children. The results showed that children in the research community have a chronological awareness of a continuous evolutionary path through age advancing.